DEVELOPING AN INTERACTIVE MATHEMATICS GAME USING SCRATCH PROGRAMMING - Nurul Syuhada, Joini (Universiti Malaysia Sarawak (UNIMAS), 2015)
Mostly students perceived learning mathematics is difficult. Hence, it is essential for parents and teachers playing their part to attract the students' interests. In the globalization of the modern world, there are lots of technologies have been developed by new Information Technology (IT) generation to make life easier. As what people said, The information is all at the finger tip". Thus, the method of integrating the elements of technology with a learning process is a new approach to capturing the students' interest. The most suitable approach to be used is developing an interactive game. The purpose of this project is to create a new approach to teaching the children in learning mathematics and provide a strong foundation for them on their high-level learning. The target group will be the children from the age of 5 to 9 years old. In addition, the Scratch programming will be used to develop new skills in children and capture their interests in exploring IT skills and field.